DNA-intercalating antiphage molecules trigger abortive infection through mutual destruction and synergize with bacterial immunity - Larissa Ernst; Cornelia Gätgens; Bente Rackow; Nadiia Pozhydaieva; Elyès Gaaloul; Aileen Krüger; Johannes Seiffarth; Michelle Bund; Vivien Joisten-Rosenthal; Dietrich Kohlheyer; Björn Usadel; Alexander Harms; et al. (Proceedings of the National Academy of Sciences, 2026)
Bacteria deploy diverse antiphage defense systems, including small bioactive molecules providing protection at the multicellular level. DNA-intercalating anthracyclines, such as daunorubicin, exhibit broad antiphage activity, but the underlying mechanism has remained elusive. Here, we systematically screened the Escherichia coli BASEL phage collection to elucidate the mode of action of DNA-intercalating antiphage molecules. We identified taxonomically distinct clusters of susceptible viral groups and show that for the Tequintavirus Bas33 ( Markadamsvirinae ), daunorubicin blocks infection after first-step transfer. In the presence of daunorubicin, continued expression of pre-early genes leads to abortive infection via “mutual destruction,” where both phage and host succumb. Analogous abortive-infection phenotypes occur across taxonomically diverse phages exposed to chemically distinct DNA-intercalating molecules. Notably, we show that daunorubicin synergizes with downstream nucleic acid-targeting defenses underscoring context-dependent outcomes. Together, these findings reveal how chemical defense contributes to the multilayered antiviral immunity and highlight the intricate interplay between mechanistic inhibition and infection outcome.